Kepemimpinan Notaris dalam Mencegah Maladministrasi yang Dilakukan oleh Karyawan Kantor Notaris - Muhammad Roykhan Rashif Aulia (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The notary, as a public official authorized to produce authentic deeds, holds a central role in ensuring legal certainty while simultaneously managing the internal performance of the notary office. In practice, the involvement of employees in administrative and technical processes creates potential risks of maladministration, including negligence, abuse of authority, and unlawful acts that may result in legal consequences for both clients and the notary. These conditions highlight the importance of leadership in establishing effective internal control systems and maintaining professional ethics. Using a normative-empirical approach, legal analysis of statutory regulations is combined with field data obtained through interviews and literature review to examine the role of notary leadership in preventing maladministration. The findings indicate that effective leadership is reflected in structured task distribution, supervision mechanisms, internal control implementation, and the development of an organizational culture based on accountability and transparency. Maladministration committed by employees may lead to civil, administrative, and criminal liability, which in certain conditions can also implicate the notary as the office leader. Strengthening managerial capacity, legal awareness, and professional ethics emerges as a key preventive strategy in minimizing administrative violations. These findings contribute to the development of notarial studies by emphasizing the strategic role of leadership as a preventive instrument in legal practice.